2018
DOI: 10.7567/jjap.57.04fb05
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of metal-atom diffusion in electric field at metal/insulator interfaces: First-principles study

Abstract: Metal-atom diffusion from metal electrodes into SiO 2 in electric fields was studied using first-principles calculations. It was shown in the case without electric field that the diffusion barrier of a metal atom is mainly made of the cohesive energy of bulk metal layers, while the shape of the diffusion potential reflects the hybridization of the metal-atom state with metal-induced gap states (MIGSs) and the electron transfer between the metal atom and the electrode. We found that the metal-atom diffusion is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…40) Other calculation details can also be seen in our previous papers. [18][19][20][41][42][43] 3. Results and discussions…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40) Other calculation details can also be seen in our previous papers. [18][19][20][41][42][43] 3. Results and discussions…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…This is because the metal atom is stable in metal layers owing to the attractive metallic interaction between metal atoms originating from the cohesion of bulk metals. 43) This result indicates that the penetration speed of metal atoms becomes much slower from metal layers than from vacuum.…”
Section: Effects Of Interaction Between Metal Atoms On Penetration An...mentioning
confidence: 98%
“…This is because superlattice geometry with the same two interfaces can avoid the unintentional electric field caused by electron transfer between two slab surfaces. 13,14) The superlattice is made of the alternative stacking of 9-11 monolayer TiN, 1-3 ILs and 25 monolayer Ge. The calculated lattice constants of bulk Ge and TiN are 5.64 and 4.26 Å, respectively, which well reproduces the observed values of 5.658 and 4.238 Å.…”
Section: Model and Methods Of Calculationmentioning
confidence: 99%
“…[9][10][11] On the other hand, such penetration property in electric fields is used to produce metal nanowires in insulators, which connect two electrodes and thus are promising for resistive memory applications. [12][13][14] In our previous works, 15,16) we studied the diffusion of metal atoms around metal/SiO 2 interfaces in electric fields by the first-principles calculation and clarified that the metalatom penetration is markedly accelerated by the applied electric field. In particular, we showed that the potential barrier for penetration decreases almost linearly with increasing the electric field for metal atoms like Ag, Au, Al, and Pt, and such behavior is explained by considering the penetration depth of metal-induced gap state (MIGS) 1,17,18) and assuming the constant ionization charges of metal atoms during the diffusion.…”
Section: Introductionmentioning
confidence: 98%